2021
DOI: 10.1136/annrheumdis-2021-220709
|View full text |Cite
|
Sign up to set email alerts
|

Impaired fertility in men diagnosed with inflammatory arthritis: results of a large multicentre study (iFAME-Fertility)

Abstract: ObjectivesThe impact of inflammatory arthritis (IA) on male fertility remains unexplored. Our objective was to evaluate the impact of IA on several male fertility outcomes; fertility rate (number of biological children per man), family planning, childlessness and fertility problems.MethodsWe performed a multicentre cross-sectional study (iFAME-Fertility). Men with IA 40 years or older who indicated that their family size was complete were invited to participate. Participants completed a questionnaire that incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 47 publications
4
17
0
2
Order By: Relevance
“…A detailed description of the differences in pregnancy characteristics between the study groups is presented in Table 1 . In line with our previous findings [ 8 ], pregnancies after IA diagnosis were characterized by a statistically significant longer time to pregnancy (TTP) [6.99 ( s . d .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…A detailed description of the differences in pregnancy characteristics between the study groups is presented in Table 1 . In line with our previous findings [ 8 ], pregnancies after IA diagnosis were characterized by a statistically significant longer time to pregnancy (TTP) [6.99 ( s . d .…”
Section: Resultssupporting
confidence: 91%
“…This study is part of the iFAME-Fertility study [ 8 ]. Briefly, the iFAME-Fertility study is a multicentre cross-sectional study that was primarily designed to evaluate the impact of IA on the male fertility rate (total number of children per man).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In men with inflammatory arthritis, the fertility rate significantly reduced with longer disease duration and also as compared to the general population. It was interesting to note that, along with reduced fertility rates, childlessness, both voluntary and involuntary, was also higher in these men, with the ones with an earlier disease onset having a higher probability of childlessness [29].…”
Section: Age and Male Fertility In Inflammatory Arthritismentioning
confidence: 98%
“…Rheumatic disease can also affect sexual function and reproduction in men, with sexual dysfunction reported in a higher proportion of men with rheumatological conditions compared with healthy controls [ 12 14 ]. In addition, the recently conducted multicentre, cross-sectional iFAME-Fertility study found that participants diagnosed with inflammatory arthritis before and during their peak reproductive age had a lower fertility rate, a higher childlessness rate and an increased frequency of fertility problems, compared with those who were diagnosed after their peak reproductive age [ 15 ]. Importantly, some treatments for RA (and IBD) may also affect sexual and reproductive health [ 16 ].…”
Section: Rationale For Patient Selectionmentioning
confidence: 99%